Formação continuada docente em nível de pós-graduação lato sensu: estudo de caso em uma instituição de ensino do Distrito Federal - Oliveira, Alexandra Lins de (2025)
Teacher training is a challenge, and continuing education presents its obstacles in the same way. Continuing education is a fundamental part of a teacher's identity, in the pursuit of constant learning and improvement of their knowledge and practices. In their professional practice, teachers require training that is effective, critical, proactive, inclusive and contemporary, with a view to keeping pace with the social, cultural and technological transformations of both the school and its students. The teacher needs to be prepared for the day-to-day life of the classroom, as there they find a diversity of situations and individuals who bring their baggage, their cultures and their particular knowledge. Within the Teacher Training line, in the Postgraduate Program in Education, Strict Sense from the Catholic University of Brasília (UCB) this research yousaw as objective analyze a continuing education of teachers in courses Broad Sense distance learning at a Higher Education Institution in the Federal District as an organizational method, understood as the organization and implementation of this offer, Broad Sense, by the IES and the contribution of these courses researched in the academic and professional roles of these teachers. The methodological approach adopted was mixed (qualitative quantitative), of an applied nature, descriptive and exploratory type on the case study and the analysis of structured questionnaires to understand teachers' perceptions about the contribution of Postgraduate courses to their professional training. The collected data were analyzed using Discursive Textual Analysis (ATD). The theoretical framework was supported by reference authors in the area of continuing education – Gatti (2010; 2021), Nóvoa (1991; 1992; 2011), Pimenta (1996;1997; 1999), Late (2012), as well as by bibliographic research – Gouveia (2013), Maricato (2020) and Souza (2013), among others. The research problem addresses whether the courses of Broad Sense teacher training serve as a means to promote the development of these professionals' training and their performance in education. From the analysis of the data, it was evident that continuing education remains a central element in the professional development of teachers. However, despite the existence of programs, projects and actions promoted, there are still significant difficulties in accessing and completing Postgraduate courses.